IMPROVING STUDENTS' ABILITY IN WRITING RECOUNT PARAGRAPH THROUGH PEER ASSESSMENT STRATEGY FOR THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 SUKASADA IN ACADEMIC YEAR 2013/2014 - ., Ni Wayan Kristina; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian tindakan kelas ini bertujuan untuk meningkatkan kemampuan siswa dalam menulis paragraf recount di kelas VIII di SMP Negeri 1 Sukasada dengan menggunakan strategi Peer Assessment. Subjek dari penelitian ini adalah kelas VIII G di tahun pelajaran 2013/2014. Jumlah subjek penelitian adalah 30 siswa dengan 25 siswa perempuan dan 5 siswa laki-laki. Penelitian ini terdiri dari dua siklus; setiap siklus terdapat empat langkah yaitu perencanaan, tindakan, observasi, dan refleksi. Data diperoleh melalui empat jenis instrumen yaitu: wawancara, catatan kegiatan, kuesioner, dan tes. Kriteria Ketuntasan Minimal adalah 73, tetapi kebanyakan siswa mengalami masalah dalam menulis yang ditemukan pada observasi awal seperti yang ditunjukkan oleh skor rata-rata siswa yaitu 66.17 (kategori tidak cukup). Setelah diberikan tindakan, nilai rata-rata siswa meningkat mencapai 77.07 pada siklus I yang dikategorikan cukup. Akhirnya, skor rata-rata siswa dapat mencapai kriteria bagus dengan nilai 84.90 pada siklus II. Dari hasil observasi, ditemukan bahwa strategi Peer Assessment membantu siswa untuk meningkatkan kemampuan menulis siswa dalam mengembangkan ide, mengorganisasi ide, menggunakan tata bahasa yang tepat dan mekanik. Hasil ini juga didukung oleh sikap positif siswa terhadap penerapan strategi Peer Assessment.Kata Kunci : Kemampuan Menulis, Strategi Peer Assessment. This classroom-based action research aimed at improving students’ ability in writing recount paragraph of the eighth grade students of SMP Negeri 1 Sukasada by using Peer Assessment Strategy. The subjects of the study were students of class VIII G in academic year 2013/2014. The total number of subjects was 30 students consisting of 25 female and 5 male students. This study was conducted in two cycles; each cycle involved four steps, namely planning, action, observation, and reflection. The data were obtained through four kinds of instruments namely: interview guide, researchers’ diary, questionnaire and test. The school minimum passing grade was 73, however the majority of students Wet preliminarily found to have problem in writing as revealed by the average score of 66.17 (insufficient category. After the treatment was conducted, students’ mean score increased to 77.07 in cycle I which categorized as sufficient. Finally, the students’ mean score could reach a good criterion which was 84.90 in cycle II. From the observation, it was found that Peer Assessment Strategy helped them improve their ability in developing idea, organizing idea, using appropriate language and mechanics. This result was also optimized by the students’ positive attitude toward the implementation of Peer-Assessment strategy. In addition, Peer Assessment strategy could motivate and improve their ability in writing a recount paragraph.keyword : Key Words: Writing Ability, Peer Assessment Strategy.